Probiotics alleviate depressive behavior in chronic unpredictable mild stress rat models by remodeling intestinal flora. Issue 8 (19th May 2021) - Li, Qiufeng; Li, Li; Niu, Xueqin; Tang, Chunling; Wang, Huaizhi; Gao, Jing; Hu, Jian
Abstract : Objective: To explore the effects of probiotics on depressive behavior in a chronic unpredictable mild stress (CUMS) rat model by remodeling intestinal flora. Methods: Twenty-four male SD rats aged 6–8 weeks were randomly divided into four groups: control group, depression group (CUMS), depression+paroxetine group (Paro) and depression+probiotics group (Pro). Sucrose preference, open field and forced swimming tests were used to assess depression-like behavior in rats. ELISA was used to detect the levels of adrenocorticotropic hormone (ACTH), and corticosterone, norepinephrine and 5-hydroxytryptamine in rat serum. Real-time PCR was used to determine the changes of Lactobacillus, Bifidobacterium, Enterococcus faecalis and Escherichia coli in rat cecum. Results: Compared with the control group, CUMS led to significant decreases of body weight, total traveled distance, duration in central area, immobility time, norepinephrine and 5-hydroxytryptamine contents in hippocampal tissues, as well as Lactobacillus and Bifidobacterium in the cecum. It also resulted in marked increases of the contents of E. faecalis and E. coli in the cecum, ACTH and corticosterone contents in the serum of rats. Paroxetine and probiotic treatment each diminished or prevented these changes. Conclusion: By remodeling intestinal flora, probiotics can reduce the CUMS-induced depressive behavior of rats, increase the levels of norepinephrine and 5-hydroxytryptamine, and inhibit the expression of ACTH and corticosterone. Significantly, the effect of both paroxetine and probiotic on microorganisms is similar.